Stale economic news, media and the stock market - Birz, Gene (Journal of Economic Psychology, 2017)
I employ a classification of headlines from newspapers and wire services to examine whether stale macroeconomic news affects stock prices. Unlike with individual stocks, the cost of obtaining information about major economic releases is relatively low. Thus, stock prices should adjust to economic news announcements prior to their coverage in newspapers. I find statistically and economically significant relationship between stale news stories on unemployment and next week's S&P 500 returns. This effect is then completely reversed during the following week. These findings show that investors are affected by salient information and support the hypothesis that investors overreact to stale macroeconomic news reported in newspapers. (C) 2017 Elsevier B.V. All rights reserved.
24 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000407528400007, lens.org/050-610-145-723-552 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Attention; Efficient markets; Macroeconomic announcements; Media; Salience; dept.eco; dept.fin

Dynamic responses and tail-dependence among commodities, the US real interest rate and the dollar - Huang, Wanling; Mollick, André Varella; Nguyen, Khoa Huu (Empirical Economics, 2017)
5 citations (Crossref) [2023-10-31]
Keywords: dept.fin

Examining the dynamic linkages of performance and volatility of REIT returns - Dania, Akash; Dutta, Sandip (The Journal of Wealth Management, 2017)
This article extends the literature on the financial performance of real estate investment trusts (REITs) by examining whether U.S. REIT returns are impacted by global REITs and other real estate subsectors, such as the U.S. Real Estate Index (USRE) and the U.S. Mortgage Finance Index (USMF). The authors also explore the issue of volatility transmission and the asymmetric effect of volatility spillover on U.S. REIT returns from innovations originating in other real estate subsectors and Global REITs. Results suggest that U.S. REITs are impacted by USRE and USMF returns. There is also evidence of volatility spillover from key real estate constituents-that is, USRE and USFM returns and global REIT markets. These results can be attributed to the changing dynamics of the real estate sector and the gradual integration of the global real estate sector as an asset class. These findings have strong implications for constructing global portfolios including REITs.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/141-751-771-127-625, pop00357 tex.type: [object Object]
Keywords: dept.eco; dept.fin

Institutional ownership and the spillover effects of shareholder activism - Jory, Surendranath; Ngo, Thanh; Nguyen, Khoa Huu (International Journal of Corporate Governance, 2017)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/018-553-764-759-222, pop00160 tex.type: [object Object]
Keywords: dept.fin